A longitudinal study of women's representations and experiences of pregnancy and childbirth. (December 2021) - Gagnon, Raymonde
Abstract: Objective: To explore women's representations of pregnancy and childbirth and how these representations are constructed and have changed. Background: In the 1980s, many women in Quebec demanded that the birthing process be both demedicalised and humanised, resulting in the legalisation of the midwife profession while expanding their choices over birthing locations within the public health system (e.g., birthing centres, the home, or hospitals). Birth-related technologies were also improving at that time. Nearly 40 years later, we wanted to learn about their perceptions. Method: This qualitative and contextualised phenomenological study surveyed 25 first-time mothers who had received care from midwives, general practitioners, or obstetricians. Each participant met with the researcher twice during her pregnancy and once after giving birth to engage in narrative conversations, which were analysed from an interdisciplinary viewpoint (socio-anthropology). Findings: Participant perceptions of pregnancy varied. Some saw it as a state that distorted the body, while others saw it as a long period of struggle with a compulsory step that was also fascinating and/or even happy. Women undergo an incremental process of change before contemplating childbirth, and typically undergo a transitional period when nearing the event itself. They may think of childbirth as joyful and/or painful. Representations are built intersubjectively through influences involving family, the media, and care providers. Stories from their mothers, therefore, created undeniable impressions. Conclusion: In a context heavily influenced by technology, easy pregnancies and/or childbirth events are typically deemed "lucky." This negatively reinforces both the cultural and intergenerational values transmitted regarding these events.